PENGARUH PENGGUNAAN METODE JARIMATIKA TERHADAP KOGNITIF SISWA KELAS III MIN 39 PIDIE PADA MATERI OPERASI HITUNG PERKALIAN BILANGAN - Junaidah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
This study aims to determine the effect of the jarimatics method on the cognitive of students 3rd grade at MIN 39 Pidie in the matter of multiplication arithmetic operations. This type of research is experimental research with a pre-Experimental One Group Pretest-Posttest research design, which are giving tests before and after being treated. The sample of this research was 14 students of 3rd grade MIN 39 Pidie. Data collection techniques used were tests and interviews. The results of the study at MIN 39 Pidie obtained the calculation of the t test where the sig. 2-tailed, namely 0.000 <0.05, obtained t count = 5.551 while t table with df 13, at a significant level of 5%, which is 2.160. Thus t-count> t-table (5,551 > 2,160) which means that Ha in this study is accepted and Ho is rejected. Therefore it can be concluded that there is an influence of the jarimatics method on the cognitive of 3rd grade students at MIN 39 Pidie in the matter of multiplication arithmetic operations